Dynamic and Statistical Features of Internal Solitary Waves on the Continental Slope in the Northern South China Sea Derived From Mooring Observations. Issue 6 (21st June 2019) - Chen, Liang; Zheng, Quanan; Xiong, Xuejun; Yuan, Yeli; Xie, Huarong; Guo, Yanliang; Yu, Long; Yun, Shengjun
Abstract: For investigation of internal solitary waves (ISWs) in the South China Sea (SCS), most cruise observations are concentrated from Luzon Strait to Dongsha Atoll in the northeastern SCS but few on the continental slope far away from the west of Dongsha Atoll. In this study, we use 1‐year long mooring data to determine dynamic and statistical features of the ISWs on the shelf slope of the northwestern SCS. The analysis results of the mooring data reveal that the ocean internal waves on the shelf slope of the northwestern SCS have physical properties of highly nonlinear waves, which are well described by the solutions of the Korteweg‐de Vries equation. The mean nonlinear phase speeds of mode‐1 and mode‐2 ISWs are 1.38 ± 0.14 and 0.66 ± 0.12 m/s, respectively. The major direction of mode‐1 ISWs is northwestward 305° ± 21°. Strong ISW currents force the major direction of total current velocities to turn 67.5° in the upper layer and 135° in the lower layer. The monthly occurrence frequency distribution of ISWs shows a peak in July with a maximum frequency of 16.2% and a trough in March with a minimum frequency of 3.3%. Mode‐2 ISWs appear most in December, accounting for 50% of total mode‐2 ISWs. The largest mode‐2 ISW on record up today with the depressed amplitude as large as 91 m, and the elevated amplitude of 73 m was observed at mooring station. These new findings and new data are of significance to local internal wave prediction model development. Plain Language Summary: Unlike the sea surface waves, the ocean internal waves are a sort of wave motions occurring in the ocean interior. Strong internal waves carry strong currents and huge power, which may greatly impact the normal ocean and cause harm to underwater navigation and ocean engineering facilities. Thus, it is a necessary work to clarify the internal wave activities in an area of interest. We deployed a chain of instrument system moored at the sea floor on the continental slope of the northwestern South China Sea, where is rich in oil and gas resources, to observe the internal waves for 1 year from June 2016 to July 2017. Using the data of observed 684 internal waves, we analyze their physical properties and statistical features. The results indicate that (1) the observed waves have typical features of internal solitary waves, (2) the maximum amplitude reaches near 100 m, and (3) strong internal wave currents force the major direction of normal current to turn about 70° and 135° in the upper and lower layers, respectively, and March and July are trough and peak months for internal wave occurrence. These data and results are of significance for underwater navigation safety and ocean engineering designs. Key Points: Nonlinear properties of mooring‐measured mode‐1 and mode‐2 IWs and wave packets in SCS are verified by KdV equation solutions Statistical features of occurrence frequency, amplitudes, and phase speeds of ISWs are derived from the 1‐year long mooring data Modulation of the internal waves to background current is measured for ocean engineering applications